The rationale and scope for privatisation in Ireland - McDowell, Moore (Statistical and Social Inquiry Society of Ireland, 2000)
The public debate over privatisation in Ireland over the last decade has single-mindedly avoided any serious intellectual analysis of the rationale behind the process in the sense of the issue of whether it is per se a desirable economic objective. There has been no debate at any theoretical level about the mechanisms of privatisation and there has been little by way of evaluation of the limited experiments in privatisation.
Symposium on market liberalisation in Ireland: competition, privatisation and regulatory issues
Read before the Society, 20 January 2000
Keywords: Market liberalisation; Privatisation; Government regulation; Competition policy; 314.15